Herança da resistência do acesso AC-02 às raças 1 e 5 de Podosphaera xanthii em meloeiro - Ricarte, Anânkia de Oliveira (2016)
Powdery mildew is a disease that causes substantial losses in melon production around the world. Obtaining resistant cultivars is possible through introgression of alleles in the breeding program. In this study, it was investigated the inheritance of resistance of AC-02 accession to races 1 and 5 of Podosphaera xanthii in cross with susceptible cultivar ‘Védrantais’, under greenhouses conditions. The segregations ratios for resistance/susceptibility observed in the different populations (F1, F2, RC1 and RC2) indicated a monogenic and dominant inheritance in AC-02 to races 1 and 5. The distance between the gene controlling resistance to race 1 (px1-ac02) and the gene which confers resistance race 5 (px5-ac02) is 28.5 cM.